Being there and being with them: the effects of visibility affordance of online short fitness video on users’ intention to cloud fitness - Chen, Xuewei; Zhu, Yuyi; Xu, Xinyue (Frontiers in Psychology, 2024)
A great deal of research has explored the correlation between media use and health-promoting behavior by examining the motivation of individuals and the credibility of influencers. However, the role of media affordance has thus far been largely overlooked. To fill this gap, this study employs the stimulusorganism-response model to investigate how and under what condition visibility affordance influences the intention to exercise with fitness influencers in the context of cloud fitness. The results of a web survey of 456 viewers of online short fitness videos reveal that visibility affordance is positively related to the intention to exercise with fitness influencers. Additionally, both the sense of social presence and the sense of immersion positively mediate the relationship between visibility affordance and the intention to exercise with fitness influencers. Furthermore, the perceived popularity of the influencer positively moderates the relationship between social presence and the intention to exercise with fitness influencers and moderates the mediating role of social presence. Consequently, the findings of moderated parallel mediation analyses offer noteworthy implications for the cloud fitness literature and individuals' intentions to engage in digital exercise.